2021
DOI: 10.1007/s42690-021-00561-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of whitefly (Bemisia tabaci) proteins interacting with Tomato leaf curl Bangalore virus coat protein gene using Y2H system

Abstract: Tomato leaf curl Bangalore virus (ToLCBV) (Geminiviridae) causes the economically important tomato leaf curl virus disease (ToLCVD), and is transmitted by the whitefly, Bemisia tabaci (Gennadius) (Aleyrodidae: Hemiptera). Successful transmission of the virus by the insect requires safe translocation of the virus through different barriers inside the vector. During the translocation, the viral coat protein will interact with many whitefly proteins, while a few of them are beneficial to virus (e.g. heat shock pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…A recent study also found that tomato leaf curl Bangalore virus (ToLCBV) CP showed interactions with 102 distinct whitefly proteins (B. tabaci Asia 1). These proteins included HSP70, GroEL, enolase, nucleoproteins, lachesins, vitellogenin, succinate dehydrogenase, apolipophorins, salivary secreted proteins, 40s ribosomal proteins, tropomyosin, sorbitol dehydrogenase, GTP cyclohydrolase, dipeptidyl peptidase, annexin, E3 ubiquitin, and others [64]. Some of these proteins might be helpful for the virus and some favor the whiteflies.…”
Section: Whiteflies-associated Virus Receptorsmentioning
confidence: 99%
“…A recent study also found that tomato leaf curl Bangalore virus (ToLCBV) CP showed interactions with 102 distinct whitefly proteins (B. tabaci Asia 1). These proteins included HSP70, GroEL, enolase, nucleoproteins, lachesins, vitellogenin, succinate dehydrogenase, apolipophorins, salivary secreted proteins, 40s ribosomal proteins, tropomyosin, sorbitol dehydrogenase, GTP cyclohydrolase, dipeptidyl peptidase, annexin, E3 ubiquitin, and others [64]. Some of these proteins might be helpful for the virus and some favor the whiteflies.…”
Section: Whiteflies-associated Virus Receptorsmentioning
confidence: 99%